THE FINGERPRINT OF SEAWATER CIRCULATION IN A 500-METER SECTION OF OCEAN CRUST GABBROS - IMPLICATIONS FOR MANTLE PLUME SOURCES - Hart S.R.; Blusztajn J.; Dick H.J.B.; Meyer P.S.; Muehlenbachs K. (My University, 1999)
A novel strip-sampling technique has been applied to the 500-m gabbroic section drilled at site 735 during Leg 118. Twenty-two continuous strips of 1.1- to 4.5-m length were cut longitudinally from the core, allowing for a more representative sampling of this section of the deep ocean crust. A full suite of trace element and isotopic (Sr, Nd, Pb, Os, δ18O) analyses were conducted on these strip samples; for comparison, analyses were conducted on a small suite of protolith samples, selected for their fresh and unaltered appearance. Amphibole, diopside, and plagioclase from 18 vein samples were also analyzed for Sr and Nd isotopes. Although the evidence for a seawater component in these gabbros is clear (87/86 Sr up to 0.70316; 206/204 Pb up to 19.3; δ18O down to 2.0%%; 187/188 Os up to 0.44), the trace element signatures are dominated by magmatic effects (infiltration and impregnation by late-stage melts derived locally or from deeper levels of the crust). The average upper 500 m 735B gabbro section is somewhat lower than average N-MORB in trace elements such as Ba (30%), Nb (50%), U (40%), and heavy REE (Yb and Lu, 30%), but somewhat enriched in others such as La (23%), Ce (24%), Pb (23%), and Sr (40%). Although the section is largely comprised of cumulate gabbros (Natland et al., 1991), and many of the strip samples show marked Sr and Eu anomalies (plagioclase cumulation), the average composition of the total 500 m section shows no Sr or Eu anomalies (<1%). This implies that there has been local separation of melt and solids, but no large scale removal of melts from this 500-m gabbro section.